STRATEGI PENINGKATAN PELAYANAN MENGEMBALIKAN KEPERCAYAAN MASYARAKAT KEPADA LEMBAGA PENDIDIKAN ISLAM PONDOK PESANTREN - Gunawan , Virgo; Mardisentosa, Bambang; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the strategic efforts of the Babus Salam Islamic Boarding School to restore public trust by improving service quality. The background to this research is based on increasing competition among Islamic educational institutions, the appeal of the government's free school program, and the shift in parental preferences toward practical, skills-based education. Babus Salam, as an Islamic boarding school that adheres to traditional values, faces the challenge of maintaining its identity while adapting to the demands of modern education. This research uses a descriptive qualitative approach with a single case study design. Data were collected through in-depth interviews with six key informant groups: the foundation leadership, the principal, teachers, alumni, active students, and parents/guardians. Data analysis used the SERVQUAL model, which encompasses the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. This analysis was combined with a SWOT analysis to identify the institution's strengths, weaknesses, opportunities, and threats. The research findings indicate that the primary strengths of Islamic boarding schools lie in their strong Islamic values, 24-hour dormitory system, charismatic kyai (Islamic teachers), and the emotional closeness between the teachers and students. However, weaknesses identified include limited sanitation facilities, a lack of air conditioning in classrooms, the absence of a formal monitoring system, and low alumni engagement. External threats include competition with modern Islamic boarding schools, the attractiveness of free public schools, negative perceptions stemming from issues at other Islamic boarding schools, and the rapid flow of information through technology. This study concludes that restoring public trust requires a comprehensive strategy encompassing improvements to physical infrastructure, strengthening managerial systems, enhancing human resource competencies, optimizing public communication, and integrating practical skills into the curriculum. These findings provide theoretical contributions to the development of strategic management literature on Islamic education, as well as practical recommendations for stakeholders and policymakers in strengthening the quality and competitiveness of Islamic boarding schools. Keywords: Service Quality, Public Trust, Strategic Management, Islamic Boarding Schools, SERVQUAL, SWOT.